Influence of COVID-19 restrictions on student satisfaction with undergraduate pathology teaching in an Australian University - Rodrigo, Chaturaka; Herbert, Cristan; Saunders, Darren; Thomas, Shane; Polly, Patsie (Frontiers in Education, 2022)
Introduction Almost three years into the COVID-19 pandemic, it is important to reflect on student perceptions of online teaching, and more specifically, if mobility restrictions imposed as public health measures significantly influence how students perceive online teaching. The aim of this study was to investigate if student perceptions of teaching quality of undergraduate courses would differ when evaluated at times of increasing or relaxing COVID-related mobility restrictions. Methods We compared student feedback for two third-year undergraduate Pathology courses taken as part of a Bachelor of Medical Sciences / Science degree in an Australian University from 2019 to 2021. Quantitative feedback on five domains (overall satisfaction, belongingness within a learning community, satisfaction with assessments, adequacy of learning resources, satisfaction with teacher feedback) were categorised into groups based on calendar year or prevailing COVID restrictions (times with no, increasing or relaxing restrictions), and compared. There were no significant changes to the course content during this time, but face-to-face teaching in 2019 changed to predominantly online teaching in 2020 and 2021. Results Feedback scores were significantly better (p<0.017) at times of increased COVID restrictions compared to times with relaxing COVID restrictions across all five domains assessed. Interestingly, when grouped by calendar years (instead of prevailing COVID restrictions), there were mostly no significant differences in the feedback scores, despite the shift to online teaching in 2020/21. Conclusion At times of increasing mobility restrictions, students may appreciate the consistency offered by well-structured online teaching but when restrictions are relaxed, online-only teaching may not meet their expectations. The teaching methods need to adapt to prevailing situation by focusing on more hands on and face-to-face teaching when circumstances allow it.